Kataplana celeretrix n. sp. (Platyhelminthes: Proseriata: Otoplanidae) from the Coast of North Carolina, USA - Bursey, Joseph; Smith, Julian P.s.; Litvaitis, Marian (Zootaxa, 2012)
Kataplana celeretrix is described as a new species of proseriate flatworm belonging to the Otoplanidae. This species was found in low-tide-level surface sediments at two high-energy beach sites in North Carolina and is unique among described Otoplanidae in possessing post-pharyngeal germaria. In addition, we consider the intermediate taxonomic position that this new species occupies between Parotoplaninae and Otoplaninae, and point to the utility of confocal microscopy in routine species descriptions.